Headache with Focal Neurological Signs - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Robert Debre Hospital and Paris Diderot University, Paris, France, and Basildon University Hospital, Essex, UK, conducted a prospective study of 101 children aged 6-18 years presenting to the ED of a tertiary hospital with moderate to severe headache and focal neurologic deficit with focal brain disturbance.